Vestibular dysfunction in chronic suppurative otitis media patients with sensorineural hearing loss - Mohamad, Adam (2020)
Objectives: Chronic suppurative otitis media (CSOM) may cause sensorineural hearing loss (SNHL) due to effect on cochlea, as well as vestibular dysfunction due to entrance of inflammatory agents and toxins through the round window. Our study was aimed to determine the prevalence of vestibular dysfunction in CSOM patients, with and without SNHL as well as the association between vestibular dysfunction and CSOM with SNHL. Methods: This was a cross sectional study involving 184 patients with CSOM, aged from 15 till 55 years (92 CSOM patients with SNHL, and 92 CSOM patients without SNHL). Hearing test was done using conventional pure tone audiometry followed by video head impulse test (VHIT) for the balance assessment Results: A total of 184 participants; 92 CSOM with sensorineural hearing loss and 92 CSOM without sensorineural hearing loss, participated in the study. The prevalence of vestibular dysfunction in CSOM patients with SNHL was 33.7%, and prevalence of vestibular dysfunction in CSOM without SNHL was 31.5%. There was insignificant association between vestibular dysfunction and CSOM with SNHL (p>0.05). Conclusions: Overall, there was a significant number of patients with CSOM having vestibular dysfunction, however there is no significant association between vestibular dysfunction and CSOM with SNHL.